Direct radiative forcing by aerosols over Southern Africa - Queface, Antonio Joaquim (My University, 2013)
A thorough understanding of the optical properties of aerosols, their spatial and temporal distribution and their radiative effects in the atmosphere, is needed for the better assessment of the impacts of aerosols on regional climate systems. Monitoring of aerosol parameters and solar radiation fluxes has been conducted in southern Africa by the AERONET programme since the middle of the last decade. These valuable data, combined with model estimates products, plus the intensive field experiments such as SAFARI 2000, provided key information, contributing towards a better overall understanding of the main characteristics of tropospheric aerosols over southern Africa and how these aerosols impact the direct aerosol forcing in the region. Two long-term AERONET sites, at Mongu in Zambia and Skukuza in South Africa, formed the core sources of data in this study. Secondary sites in Saudi Arabia (Solar Village) and United Arad Emirates (Hamin and Dhadnah) were used for comparison purposes. Aerosol optical properties and the direct aerosol radiative forcing over southern Africa both change significantly from one season to another, following the strong seasonal cycle of aerosol optical thickness (AOT). Consequently, the evaluation of aerosol forcing using static values throughout the year is not suitable for describing the aerosol climate effects in this region. Results show that the seasonal variations of aerosol optical thicknesses at 500 nm over southern Africa can be defined into three periods:  December to May with relatively clean atmospheric conditions, with monthly averages AOT values at 500 nm between 0.1 to 0.2, mainly associated with air masses from which aerosols have been washed during the wet season, and minimal regional biomass burning;  followed by a transition period towards high AOT values, from June to August, with a moderately turbid atmosphere (0.2 – 0.3);  September to November, with high levels of AOT (0.3 – 0.5) –mainly associated with biomass burning. Within this region a reversal gradient of AOT can be observed along the annual timeline; the north has higher magnitudes than the south, i.e. a north–south gradient, during the biomass-burning season and the opposite applies in the non-biomass burning season, i.e. a south–north gradient. From the currently available aerosol data, no long-term discernible trends are observable in aerosol loadings over this region. Direct aerosol radiative forcing evaluations, in southern Africa, need to take into account the differences between both the non-biomass burning and the biomass burning seasons. Direct aerosol forcing magnitudes during the biomass burning period are almost double those of the non-biomass burning at BOA and TOA. The impact of biomass burning on the direct aerosol forcing is not limited to the bottom of atmosphere (BOA), but also influences the forcing at top of atmosphere (TOA). Direct aerosol radiative forcing values for all of southern Africa are estimated at -33 W m-2 for BOA and -6 W m-2 for TOA. However, seasonal values may differ considerably from these levels. Monthly averages of direct aerosol radiative forcing at BOA are frequently less than -30 W m-2 from December to May (non-biomass burning period) with a slightly south-north gradient. From July to October, a strong north-south gradient of direct aerosol radiative forcing is observed and forcing magnitudes are frequently recorded at -50 W m-2 (and, on occasion well above that level) during September, i.e. at the peak of biomass burning. June and November are regarded as transitional months when levels move towards the higher or and lower values of forcing respectively. At TOA monthly averages of direct aerosol radiative forcing from December to May are frequently less than -9 W m-2 and, during biomass burning, direct aerosol radiative forcing values almost double. From the seasonal perspective, it is also possible to depict the reversal gradient behaviour at TOA. This study has contributed to improving the understanding and knowledge about of the direct aerosol radiative effects in this region - necessary step towards addressing the indirect and semi-direct aerosol effects. This study also emphasises the need for obtaining further data for defining the aerosol optical characterisations by regions or sub regions as demonstrated by the identifiable overall differences in the aerosol optical properties between the southern Africa and Middle Eastern regions. This process will require improving the quantity and quality of aerosol measurements at regional scales.
A thesis submitted to the Faculty of Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy February 2013
Keywords: Aerosols.; Aerosols - Environmental aspects.; Radiation.